Modern Contraceptive Use and Influencing Factors in Amhara Regional State: Further Analysis of Ethiopian Demographic Health Survey Data 2016 - Melash Belachew Asresie; Gedefaw Abeje Fekadu; Gizachew Work Dagnew; Yared Mulu Gelaw (Hindawi Limited, 2020)
Background. Ethiopia is one of the Sub-Saharan African countries with a high unmet need for contraceptives. Contraception is a good indicator of the extent to which couples have access to reproductive health services. A study on contraceptives can provide overall direction by helping to identify the obstacles in society and weaknesses in services that need to be overcome. However, little is known in Amhara region context. Therefore, this analysis was aimed to assess modern contraceptive use and influencing factors in the Amhara regional state of Ethiopia. Methods. We used secondary data analysis of the regional representative sample of women aged 15-49 years from the 2016 Ethiopian Demography and Health Survey (EDHS). A total of 2207 married reproductive-age women (15-49 years) selected using a two-stage stratified cluster sampling technique were included in this analysis. Both descriptive and logistic regression analyses were performed using STATA V.14. A 95% confidence interval was used to declare statistical significance. Results. Modern contraceptive use among married reproductive-age women was 51.3% (95% CI: 47.0-55.6). Being from households with rich wealth index (AOR = 1.6; 95% CI: 1.1-2.5), a secondary or higher level of education (AOR = 3.0; 95% CI: 1.4-6.2), and desire to space (AOR = 2.6; 95% CI: 1.9-3.7) or want no more child (AOR = 2.4; 95% CI: 1.6-3.5) were found positively associated with modern contraceptive use. On the other hand, modern contraceptive use was negatively associated with women aged 35-49 years (AOR = 0.7; 95% CI: 0.5-0.9). Conclusion. Modern contraceptive use was relatively high in the Amhara region. The odds of modern contraceptive use were higher among women with secondary or more educational levels. Women from households with rich wealth index and those who want to delay or avoid pregnancy had also more odds of using modern contraceptives. Therefore, strengthening women's and community education could improve modern contraceptive use. Moreover, more emphasis should be given for income generation activities.